Differences in Subjective Well-being Among Special-school Teachers and Regular Teachers in Ternate - Umairah, Siti; Dabi, Syam Ardhy Dabi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Improving the quality of human resources in Indonesia, especially in Ternate, a teacher plays a very important role in the field of education and has a strategic position because it is one way to create competent and quality human resources. The aim of the research was to look at the differences in subjective well-being between special school teachers and regular school teachers in Ternate. The subjects were 58 special school teachers and 61 regular school teachers with a total of 117 teachers. Based on statistical test data, the subjective well-being of regular teachers is higher with a score of 69.59% in 61 subjects and the subjective well-being of special school teachers is lower with a score of 47.46% in 58 subjects. Based on these results, it shows that there is a very significant difference in subjective well-being between special school teachers and regular school teachers, it is found that regular teachers have higher subjective well-being compared to special school teachers.